QARAQALPAQ FOLKLORÍNDA LAP JANRÍNÍŃ KÓRKEMLIK ÓZGESHELIKLERI - Berdimuratov, J.A. (ILIM hám JÁMIYET, 2025)
The article presents a wide range of scientific opinions on paws, one of the main genres of Karakalpak folklore that requires study. Also, on a special scientific and theoretical basis, the artistic features of the fairy tale genre were studied.